POLYSEMY IN COMPUTER TERMS - Nina Setyaningsih (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2011)
The development of computer and information technology resultsin the development of word meanings. Many terms in computer create multiplicity of meanings of the same words. This also deals with metaphor as the words share some common properties. This paper is aimed at examining the polysemy in computer terms driven by metaphors. The data were gathered from seven online computer articles, and there are 17 polysemous words found. The methods used to analyze the data were referential method and componential analysis. The result reveals that many terms in computer are polysemous because there are shared properties and they can be related to metaphors. Furthermore, polysemy consists of lexicon in which words are represented and the conceptual system in which the knowledge is represented through metaphors.Keywords: componential analysis, computer terms, metaphor, polysemy